Sterile processing for pharmacy technicians - Davis, Karen (St. Louis, Missouri : Elsevier/Saunders, 2014)
Covering aseptic technique and how to prepare sterile products, this book ensures safety, accuracy, and correctness of medications. Reflecting American Society of Health System Pharmacists (ASHP) competencies, this book provides principles and guidelines, laboratory exercises, and hands-on practice with actual institutional orders. Written by expert pharmacy technician educator, this book also provides checklists that map to ASHP competencies.
Includes bibliographical references and index.
Keywords: Asepsis and antisepsis; Pharmaceutical technology; Pharmacy technicians; Sterilization; Pharmaceutical Solutions; Sterilization -- methods; Drug Compounding -- standards; Pharmacists' Aides; Asepsis and antisepsis; Pharmaceutical technology; Pharmacy technicians; Sterilization